Tuberculosis of the Glans Penis: A Case Presentation with Review Literature - Nisar Ahmed Shaikh, Aamir Ali Shaikh, Hameed-ur-Rehman Bozdar, Riaz Hussain, Khob Chand Rohra, Muhammad Imran Soomro, Amanullah Abassi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tuberculosis of the glans penis is a rare occurrence., even in developing nations. Aim and Object: To review the literature and case presentation of Tb of glans penis Methodology: Pakmedinet, Pubmed and google data were searched for Tb of glans penis. Literature Review: Tuberclosis of the penis can be primary or secondary, and it might look like penile cancer, penile ulcers (granulomatous), genital herpes simplex or HIV infection. Tb of the Penis can develop after a individual who had primary pulmonary Tb and can be spread through ejaculation, contamination of endometerium secretions or clothes, as a result of a previous pulmonary Tb or Tb somewhere else. Tb of the Penis is characterised by a tiny nodule on the penis that is either painless or painful, an ulcer, a mass that progressively increasing and be swelling. Palpation of inguinal lymph nodes and erection problems of the penis can or can not observed. Normally, the patient’s voiding is normal. Biopsy or acid fast bacilli in penile discharge or positive Elisa serology or PCR for tuberculosis are used to confirm the diagnosis. Needs 6 months, pulmonary tuberculosis therapy. Conclusions: Tb of the glans penis is an uncommon occurrence. After a biopsy, antitubercular medications are the standard treatment, thus doctors should evaluate the potential of Tb of the penis in instances of penile lesions. Keywords: Tb, penis, presentatation management and review litrarature